A New Species of the Genus Phyllodistomum (Braun, 1899) (Digenea: Gorgoderidae, Looss, 1901) from Freshwater Fish Mastacembelus armatus Aurangabad (M.S.) India - Sarwat*, M. S. (Recent Research in Science and Technology, 2011)
The present paper deals with a new species of the genus PhyllodistomumÃ‚Â  [2].Viz Phyllodistomum triangulata n.sp is reported from freshwater fish Mastacembelus armatus (L.) Jayakwadi dam, Dist Aurangabad. It differs from all the earlier reported species in having the body of the fluke is dorso-ventrally flattened, anterior portion of the body is long and narrow while the posterior portion of the body is broad, expanded and nearly triangular in shape, oral sucker is sub-terminal and oval in form, ventral sucker is circular, genital pore is prebifurcal, ovary is trilobed, laurer's canal is present.